Characterization of reported legionellosis outbreaks associated with buildings served by public drinking water systems: United States, 2001–2017. (21st March 2022) - Holsinger, Hannah; Tucker, Nicole; Regli, Stig; Studer, Kirsten; Roberts, Virginia A.; Collier, Sarah; Hannapel, Elizabeth; Edens, Chris; Yoder, Jonathan S.; Rotert, Kenneth
Abstract: This study examined 184 legionellosis outbreaks in the United States reported to the Centers for Disease Control and Prevention's Waterborne Disease and Outbreak Surveillance System, from 2001 to 2017. Drinking water characteristics examined include source water type, disinfectant type, exposure setting, geographical distribution by U.S. Census Divisions, and the public water system size (population served). This study found that most of the reported drinking water-associated legionellosis outbreaks occurred in eastern United States, including 35% in the South Atlantic, 32% in the Middle Atlantic, and 16% in the East North Central Census Divisions were linked with building water systems in healthcare and hotel settings; and were associated with buildings receiving drinking water from public water systems serving >10, 000 people. Targeted evaluations and interventions may be useful to further determine the combination of factors, such as disinfectant residual type and drinking water system size that may lead to legionellosis outbreaks. HIGHLIGHTS: Most of the reported legionellosis outbreaks associated with drinking water in the United States (2001–2017) have been documented in healthcare and hotel/motel settings. Reported legionellosis outbreaks were more often associated with buildings obtaining water from large, chlorinated, surface water systems than with small systems (serving 10, 000 or fewer), using disinfectants other than chlorine and ground water sources. Graphical Abstract